Child Sexual Abuse within Educational Settings: A Qualitative Study on Female Teachers Who Sexually Abuse Their Students. Issue 11 (1st November 2020) - Steely, Mollee; Ten Bensel, Tusty
ABSTRACT: Despite growing interest, research on female sex offenders has been limited. Previous research on female sex offenders has focused on understanding behaviors, patterns, and motivations of female sex offenders overall, but only a handful of studies have specifically focused on teachers who are convicted of sexually abusing underaged students. For the present study, we examined the nature of child sexual abuse among a sample of female teachers, focusing specifically on the onset, situational context, and conclusion of these sexual abuses. We examined interviews conducted with 35 female sex offenders who used their position as a teacher to engage in a sexual abuse of underage students from 1995 to 2016 in a southern state. Based on the narratives of both victims and offenders, our findings indicated several categories of female teacher offenders including predatory, sexual friendship, and emotionally dependent. We hope the findings of the current study will help inform educational policy in efforts to prevent the occurrence of these abuses in the future.